Physical Fitness and Self Efficacy in PATHFIT 1 of Education Students - Catalan, Reym Nicole; Nillos, Charles; Guitche, Melona; Perez, Rexomar (Technium Social Sciences Journal, 2024)
Self-efficacy is an individual's belief in their ability to perform and accomplish tasks. On the other hand, physical fitness encompasses an individual's comprehensive state of bodily health and well-being. It pertains to the capacity to engage in physical activities effortlessly, efficiently, and without undue exhaustion or strain. The study aimed to determine the level of Physical Fitness and Self-Efficacy in PATHFIT 1 of Education students when grouped according to sex, year level and major field of specialization. This study used a descriptive and correlational research. The respondents were the 234 students using stratified random sampling. A standardized questionnaire used in this study for self- efficacy was taken from the general self-efficacy scale. The physical fitness questionnaire was researcher made and undergone a validation process. The salient results of the study were as follows: the level of physical fitness and self- efficacy were moderate; physical fitness significantly influenced the self-efficacy of Education students; there is no significant difference in the level of physical fitness of education students when grouped according to sex, year level and major field of specialization; and there is no significant difference in the level of self-efficacy of education students when grouped according to sex, year level and major subject. An enhancement program was formulated to better the importance of developing physical fitness and self-efficacy among students to monitor progress and changes.